Stabilisation of a highly plastic clay soil for the production of compressed earth blocks - Rix, Carl Gunther (My University, 2014)
Clay plays an important role in the suitability of soil for use in construction. The affinity of a clay for moisture makes it susceptible to shrinkage and swelling on drying and wetting and therefore problematic in terms of construction, where stability is required for the integrity of a structure to remain intact. It is therefore important to have methods of dealing with problematic clays in order to allow clays to be used as a construction material. One of the methods is known as soil stabilisation, where the properties of a soil and mainly the clay fraction are altered to make it more suitable for its intended purpose. The thesis investigates the use of a highly plastic clayey soil for the production of building blocks. Due to the clayey nature and its associated properties the soil it is not suitable in its natural state. Soil stabilisation is investigated as a method to alter the properties of the soil. The principles of soil stabilisation are presented as an introduction to the laboratory testing programme. Combinations of lime, cement and fly ash are investigated as a stabilising agent. They are investigated to determine which combination alters the properties of the soil to such an extent, that a compressed soil block produced using the combination and the clayey soil, would perform satisfactorily according to accepted standards. Combinations were designed so that comparisons could be made between blocks to determine what effect the addition of a certain stabilising agent would have on the performance of the block in terms of the tests conducted. The engineering properties of the untreated soil which are not considered suitable for use in compressed soil blocks, are significantly enhanced by he addition of the stabilising agents. The test conducted on the blocks indicate that the addition of 4% lime, 20% fly ash and 7% cement added to the soil produces a block that satisfies the criteria adopted for the research and that are generally in accord with international standards. A mineralogical analysis was also undertaken in an attempt to identify changes in the mineralogy of the soil, and particularly the clay, as a result of the addition of the three stabilising agents. This analysis was done using x-ray diffraction. Due to the nature of the clay mineral and possibly the poor crystal structure thereof, the results were disappointing. No significant change in the clay was observed to correlate with the results of the improved performance as indicated by the physical tests.